Characterization of the non-apparent clinical form in the initial phase of schistosomiasis mansoni Caracterização da forma inaparente da fase inicial da esquistossomose mansoni - Manoel Otávio da Costa Rocha; Enio Roberto Pietra Pedroso; Jayme Neves; Roberto Sena Rocha; Dirceu Bartolomeu Greco; José Roberto Lambertucci; Regina Lunardi Rocha; Naftale Katz (Revista do Instituto de Medicina Tropical de São Paulo, 1993)
In this paper the history of 115 recruits that had bathed simultaneously in streams contaminated with Schistosoma mansoni, during military maneuvers, is reported. Thirty four of the infected patients presented the initial phase of the infection diagnosed through epidemiologic, clinical and laboratorial parameters. Three out of the 34 patients did not reveal the clinical picture of the infection, thus being considered representatives of the non-apparent form of the disease. Differences between the intensity of blood eosinophilia, the area of immediate cutaneous reaction and the number of Schistosoma eggs eliminated in the stools proved not to be statistically significant (p>0.05) when the non-apparent and acute cases of schistosomiasis were compared. These cases actually may be considered evidences of the non-apparent form hitherto merely taken for granted in the literature. Foram estudados 115 recrutas que tiveram contato simultaneamente com águas infectadas pelo Schistosoma mansoni. Trinta e quatro pacientes apresentaram a fase inicial da infecção, diagnosticada através de parâmetros laboratoriais, clínicos e epidemiológicos, sendo que três deles não evidenciaram quadro clínico, sendo considerados como portadores da forma inaparente da doença. Não se verificou, entretanto, diferença estatística entre a intensidade da eosinofilia sanguínea, as áreas da reação intradérmica de leitura imediata e as médias das contagens do número de ovos de 5. mansoni eliminados nas fezes, quando se compararam os resultados obtidos em pacientes com as formas aguda e inaparente. Os casos ora descritos constituem evidenciação objetiva da forma inaparente, antes apenas presumida na literatura.